2021
DOI: 10.1002/kjm2.12449
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA‐19b targets FBXW7 to promote colorectal cancer stem cell stemness and induce resistance to radiotherapy

Abstract: Colorectal cancer (CRC) continues to be one of the most malignant cancers with a high mortality rate to date. Promoting the radio‐responsiveness of CRC is of great importance for local control and prognosis. In this study, we examined the roles of exosomal microRNA‐19b (miR‐19b) in CRC radioresistance. The regulatory role of miR‐19b in CRC stem cells and radiotherapy‐resistant cells was determined using miRNA microarray analysis, and its prognostic value was probed using the TCGA database. It was found that mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…CAFs can deliver exosomal miR-92a-3p to CRC cells, which in turn activates Wnt/β-catenin pathway by suppressing FBXW7 and Modulator of apoptosis 1 (MOAP1) and finally promotes cell stemness ( 184 ). Moreover, the exosomal miR-19b derived from CRC cells promotes stemness by inhibiting FBXW7 expression, which subsequently induces Wnt/β-catenin signaling pathway ( 193 ). In perihilar cholangiocarcinoma (pCCA), the high mobility group A1 (HMGA1) interacts with thyroid hormone receptor interactor 13 (TRIP13), and the HMGA1-TRIP13 axis promotes cell stemness by downregulating FBXW7 expression and thus stabilizing c-MYC, the latter in interplay with Wnt/β-catenin signaling ( 209 ).…”
Section: Perspectives: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…CAFs can deliver exosomal miR-92a-3p to CRC cells, which in turn activates Wnt/β-catenin pathway by suppressing FBXW7 and Modulator of apoptosis 1 (MOAP1) and finally promotes cell stemness ( 184 ). Moreover, the exosomal miR-19b derived from CRC cells promotes stemness by inhibiting FBXW7 expression, which subsequently induces Wnt/β-catenin signaling pathway ( 193 ). In perihilar cholangiocarcinoma (pCCA), the high mobility group A1 (HMGA1) interacts with thyroid hormone receptor interactor 13 (TRIP13), and the HMGA1-TRIP13 axis promotes cell stemness by downregulating FBXW7 expression and thus stabilizing c-MYC, the latter in interplay with Wnt/β-catenin signaling ( 209 ).…”
Section: Perspectives: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Thus, miR-19b has been reported to mediate resistance to oxaliplatin treatment via SMAD4, promoting proliferation and colon cancer progression [ 39 ]. Sun and colleagues showed that exosomal miR-19b induced resistance to radiotherapy and enhanced the stemness properties of CRC cells by targeting FBXW7 [ 40 ]. MiR-19b has been proposed to play a role in 5-FU resistance of CRC cells since its expression in 5-FU resistant cells was found to be upregulated in response to 5-FU exposure in these cells [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exo-miR-19b transfer from CRC to recipient cells, has been linked with enhanced stemness and radioresistance, via FBX downregulation and Wnt/β-catenin pathway activation. These results suggest that miR-19b inhibition could promote CRC cell resensitisation to radiotherapy [102]. Another radioresistance mechanism, implicating ex-miRNAs has been proposed by Chen et al CAF-derived exosomes were found to enclose miR-93-5p; the latest inhibits radiation-induced apoptosis, possibly by downregulating FOXA1 and upregulating TGFB3.…”
Section: Final Remarks and Future Perspectivesmentioning
confidence: 55%